Peningkatan Kemampuan Berkomunikasi Siswa dalam Menulis Narasi Melalui Media Gambar pada Siswa Kelas VIII - Lumbantobing, Victor Marulitua (FKIP - Universitas Dr. Soetomo Surabaya, 2016)
In writing lesson students are trained to communicate using reason and thinking on a regular basic, either expressly or impliedly. Students tend to be possive and less creative in expressing ideas or ideas in writing class, because the student are difficult to describe in detail the result of the writing. In this case need to develop strategies in the keraning by using media images. Media images can be used to enhance students skill in writing narrative, which will help students focus the object of events that have been seen in actual, and as a mean to train students reasoning. The study population was SMP Negeri 1 Tanah Merah Bankalan using a sample class VIII scholl year 2013-2014. Qualitative research design used by the type of classroom action research (CAR). The result of analysis of data obtained from the result of testing the use of media images can be increase of 20% completeness study of student data on the use of media images can be conclude that; (1) media images able to attract student to lear to write; (2) to improve students’ reasoning communicating